Rates, polarizations, and asymmetries in charmless vector-vector B meson decays. - Aubert, B; Barate, R; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2003)
With a sample of approximately 89 x 10(6) B(-)B pairs collected with the BABAR detector, we perform a search for B meson decays into pairs of charmless vector mesons (phi, rho, and K*). We measure the branching fractions, determine the degree of longitudinal polarization, and search for CP violation asymmetries in the processes B+-->phiK(*+), B0-->phiK(*0), B+-->rho(0)K(*+), and B+-->rho(0)rho(+). We also set an upper limit on the branching fraction for the decay B0-->rho(0)rho(0).